Impact of loss of NF‐κB1, NF‐κB2 or c‐REL on SLE‐like autoimmune disease and lymphadenopathy in Faslpr/lpr mutant mice. Issue 1 (14th July 2015) - Low, J T; Hughes, P; Lin, A; Siebenlist, U; Jain, R; Yaprianto, K; Gray, D H D; Gerondakis, S; Strasser, A; O'Reilly, L A
Abstract : Defects in apoptosis can cause autoimmune disease. Loss‐of‐function mutations in the 'death receptor' FAS impair the deletion of autoreactive lymphocytes in the periphery, leading to progressive lymphadenopathy and systemic lupus erythematosus‐like autoimmune disease in mice ( Fas lpr/lpr (mice homozygous for the lymphoproliferation inducing spontaneous mutation)) and humans. The REL/nuclear factor‐κB (NF‐κB) transcription factors regulate a broad range of immune effector functions and are also implicated in various autoimmune diseases. We generated compound mutant mice to investigate the individual functions of the NF‐κB family members NF‐κB1, NF‐κB2 and c‐REL in the various autoimmune pathologies of Fas lpr/lpr mutant mice. We show that loss of each of these transcription factors resulted in amelioration of many classical features of autoimmune disease, including hypergammaglobulinaemia, anti‐nuclear autoantibodies and autoantibodies against tissue‐specific antigens. Remarkably, only c‐REL deficiency substantially reduced immune complex‐mediated glomerulonephritis and extended the lifespan of Fas lpr/lpr mice. Interestingly, compared with the Fas lpr/lpr animals, Fas lpr/lpr nfkb2 −/− mice presented with a dramatic acceleration and augmentation of lymphadenopathy that was accompanied by severe lung pathology due to extensive lymphocytic infiltration. The Fas lpr/lpr nfkb1 −/− mice exhibited the combined pathologies caused by defects in FAS‐mediated apoptosis and premature ageing due to loss of NF‐κB1. These findings demonstrate that different NF‐κB family members exert distinct roles in the development of the diverse autoimmune and lymphoproliferative pathologies that arise in Fas lpr/lpr mice, and suggest that pharmacological targeting of c‐REL should be considered as a strategy for therapeutic intervention in autoimmune diseases.